Comparing the epidemiological, immunological and clinical features of extrinsic and intrinsic-type atopic dermatitis. - Harangi, F.; Adonyi, M.; Baranyai, Z.; Schneider, I.; Sebó´k, B. (European Journal of Pediatric Dermatology, 2007)
The study was meant to survey and compare the epidemiological, clinical and immunological features of the two forms of atopic dermatitis (AD) in 94 patients. Based on the total IgE and allergen-specific IgE levels and the outcome of prick-test on environmental allergens, 58 patients (61.7%) proved to be affected by extrinsic-type of AD and 36 patients (38.3%) were affected by intrinsic-type of AD. The incidence of AD was higher in girls (56.4%) and this difference was found more expressed in the intrinsic-type of AD (63.9%). The onset of the disease appeared as early as before the second year of age in extrinsic-type 65.6%, while in intrinsic-type this rate was only 36.1%. The family history proved positive in almost the same rate in both the groups, and no difference was found between the clinical symptoms of the patients in both the groups. 48.9% of patients with extrinsic-type AD were simultaneously suffering from asthma and/or hay fever, which was very rarely observed in those with intrinsic-type AD (13.9%).